2011
DOI: 10.1002/chem.201001121
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Photooxidation of Alkenes by V‐Doped TiO2‐MCM‐41: Mechanistic Insights of Ethylene Photooxidation and Understanding the Structure–Activity Correlation

Abstract: Nanoparticles of Ti(0.95)V(0.05)O(2) were found to be impregnated in the hexagonal channels of the MCM-41 host, with a distribution of some particles on the surface, thus leading to an effective variation in the particle size as a function of loading host MCM-41 matrix. These catalysts were subjected to the photocatalytic degradation of alkenes under the ambient conditions in which the photocatalytic activity varied as a function of the loading percentage of Ti(0.95)V(0.05)O(2) in the host MCM-41.This is expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Over as-prepared catalyst, ethylene adsorption leads to further dehydrogenation and ethylidyne production at temperatures between 25 and 200 °C. This was evidenced by the absorption peaks at 2925, 2866, and 1383 cm –1 and similar spectra recorded for ethylene adsorption over Pt, Rh, Pd, and Ir. The vibrations at 2961, 1626, and 1469 cm –1 suggested that molecular ethylene could adsorb intact on the catalyst surface similar to other adsorption studies. The vibration at 1593 cm –1 observed after heating to 300 °C suggests coke formation in the form of polyaromatic carbon species. , This study suggested the presence of over-reactive surface sites in the as-prepared catalysts, which may be poisoned and made to be catalytically inert through the propane pretreatment. Unfortunately, propane-treated catalysts could not be reasonably analyzed by DRIFTS due to coke deposition making the catalyst opaque.…”
supporting
confidence: 77%
“…Over as-prepared catalyst, ethylene adsorption leads to further dehydrogenation and ethylidyne production at temperatures between 25 and 200 °C. This was evidenced by the absorption peaks at 2925, 2866, and 1383 cm –1 and similar spectra recorded for ethylene adsorption over Pt, Rh, Pd, and Ir. The vibrations at 2961, 1626, and 1469 cm –1 suggested that molecular ethylene could adsorb intact on the catalyst surface similar to other adsorption studies. The vibration at 1593 cm –1 observed after heating to 300 °C suggests coke formation in the form of polyaromatic carbon species. , This study suggested the presence of over-reactive surface sites in the as-prepared catalysts, which may be poisoned and made to be catalytically inert through the propane pretreatment. Unfortunately, propane-treated catalysts could not be reasonably analyzed by DRIFTS due to coke deposition making the catalyst opaque.…”
supporting
confidence: 77%
“…4,5,6,7]. VO x (specifically including V 2 O 5 ) particles on TiO 2 are known to be particularly catalytically active [8], while doping bulk TiO 2 with transition metals [9], and particularly with vanadium [10,11,12,13], offers a route to lowering the band gap of the pure oxide (~3 eV), thus allowing photoactivation to occur with light in the visible spectral range [14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their study demonstrated that ethylene decomposition occurred via the formation of ethoxy groups, which subsequently transformed to acetaldehyde or enolates, then to acetates/formate, and finally, to CO 2 . The vanadium-doping enhanced the catalytic activity by forming more chemisorbed hydroxyl species which might have increased the average coverage and residence time of intermediates for further oxidation …”
mentioning
confidence: 99%
“…5 The vanadiumdoping enhanced the catalytic activity by forming more chemisorbed hydroxyl species which might have increased the average coverage and residence time of intermediates for further oxidation. 6 Besides the fundamental understanding of how to improve the turnover frequency of the active sites, the rational design of a nanostructured substrate with higher specific surface area and porosity, which is beneficial to mass transport, is of equal importance. For this reason, C 3 N 4 was used as a template for the synthesis of oxygen-deficient, porous TiO 2 nanosheets with Pt decoration.…”
mentioning
confidence: 99%